Optimization of the relationship of Lens Dissipation Disk and Pixel Size to Improve the Precision of the Coordinates of a Small Object Image - P. S. Baranov; A. A. Mancvetov (Известия высших учебных заведений России: Радиоэлектроника, 2016)
The optimum relation of to the pixel size providing a maximum of accuracy of an estimates of coordinates of the image centers of small-sized objects for a wide range of entry conditions: of a signal, background and reading noise levels is defined. The analysis of influence of initial shift of small-sized object on the accuracy of definition of position of his center is carried out. It is shown that if the relation of lens dissipation disk to the pixel size less than 0.8 that the error of definition of the small-sized object center considerably depends on initial shift.